Here's the question you clicked on:
zakeyadorsey
Solve 2 log2 2 + 2 log2 6 – log2 3x = 3
the log(4)(36)-log36=3
hmm ,from where you got (36) ???
i meant to put log(4)(36)-log3x=3 sorry
right now i really just don't know where to go from log144-log3x=3
Wow I would have never gotten that thank you! but thats not one of the answer choices
thay are x= 2,x=6,x=16,x=18
Lets begin step by step First we will get the power inside the log : \[\Large Log_{2}2^2+Log_{2}6^2-Log_{2}(3x)=3\] Then according the the property that i showed to you in the last Post We will combine them: \[\Large Log_{2}\frac{2^2*6^2}{(3x)}=3\] Lets change it to exponential : \[\Large \frac{2^3}{1}=\frac{2^2*6^2}{(3x)}\] Now lets change it to an equation: \[\Large \color{red}{24x=144}\] Divide by 24 \[\Huge \color{blue}{x=6}\]
ooh ok i got it thanks